Korelasi Lingkar Pinggang dengan Kadar Gula Darah Puasa, Kadar Trigliserida, dan Tekanan Darah pada Mahasiswa Fakultas Kedokteran Universitas HKBP Nommensen - Ervina Julien Sitanggang (Health and Medical Journal, 2021)
Introduction: Cardiovascular disease is the number one cause of death globally with an incidence of adolescents and young adults in Indonesia as many as 153.705 cases. Central obesity is associated with the risk of cardiovascular disease due to increase in fasting blood glucose levels, cholesterol and triglyceride levels, and blood pressure. Aims: to determine the correlation between waist circumference and fasting blood glucose levels, triglyceride levels, and blood pressure in young adults. Method: This analytic study with a cross-sectional approach involved 53 young adult subjects (18-25 years old). Waist circumference is measured using a tape measure. Blood sugar and triglyceride levels were measured using Cobas® 6000 analyzer machine from blood samples of subjects after fasting for 8-12 hours. Blood pressure data are obtained by measurement using aneroid sphygmomanometer. Results: In this study, the mean waist circumference of the research subjects was 77,4 cm. No correlation was found between waist circumference and fasting blood sugar levels (p = 0,159). However, a positive correlation was found between waist circumference and triglyceride levels (p = 0,008; r = 0,332), between waist circumference and systolic blood pressure (p = 0,049; r = 0,230), and between waist circumference and diastolic blood pressure (p = 0,017; r = 0,293). Conclusion: waist circumference is positively correlated with triglyceride levels and blood pressure, but does not correlate with fasting blood sugar levels.